2021
DOI: 10.1111/nmo.14155
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal eosinophils, mast cells, and intraepithelial lymphocytes in youth with rumination syndrome

Abstract: Background Rumination syndrome has been associated with increased duodenal eosinophils and intraepithelial lymphocytes in adults. The aims of the current study were to assess densities of antroduodenal eosinophils and mast cells and duodenal intraepithelial lymphocytes in youth with rumination syndrome and to compare cell densities in those with and without abdominal pain or early satiety. Methods Twenty‐eight youth fulfilling Rome IV criteria for rumination syndrome who had undergone endoscopy were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…As the role of mast cells in the pathology of gastrointestinal disease is still evolving, there are currently no specific criteria for their number in the normal stomach (Doyle et al, 2014; Ramsay et al, 2010; Zanelli et al, 2021). Quantification of mast cells in the healthy gastric mucosa reveals a wide range from fewer than 15 to more than 50 per HPF (Friesen et al, 2020, 2021; Hahn & Hornick, 2007; Jakate et al, 2006; Siegert et al, 2004), which makes it difficult to specify a cut‐off value for differentiating normal from pathological mucosa. In systemic mastocytosis, mast cells are often found in confluent sheets and aggregates of over 100 cells per HPF (Ramsay et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the role of mast cells in the pathology of gastrointestinal disease is still evolving, there are currently no specific criteria for their number in the normal stomach (Doyle et al, 2014; Ramsay et al, 2010; Zanelli et al, 2021). Quantification of mast cells in the healthy gastric mucosa reveals a wide range from fewer than 15 to more than 50 per HPF (Friesen et al, 2020, 2021; Hahn & Hornick, 2007; Jakate et al, 2006; Siegert et al, 2004), which makes it difficult to specify a cut‐off value for differentiating normal from pathological mucosa. In systemic mastocytosis, mast cells are often found in confluent sheets and aggregates of over 100 cells per HPF (Ramsay et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Quantification of mast cells in the healthy gastric mucosa reveals a wide range from fewer than 15 to more than 50 per HPF (Friesen et al, 2020(Friesen et al, , 2021Hahn & Hornick, 2007;Jakate et al, 2006;Siegert et al, 2004), which makes it difficult to specify a cut-off value for differentiating normal from pathological mucosa. In systemic mastocytosis, mast cells are often found in confluent sheets and aggregates of over 100 cells per HPF (Ramsay et al, 2010).…”
Section: F I G U R E 2 Legend On Next Pagementioning
confidence: 99%
“…In patients with eosinophilic esophagitis, higher tryptase levels are associated with increased frequency of nausea [11]. A recent study in pediatric patients with rumination syndrome demonstrated increased eosinophil and mast cell densities in the gastric antrum [12]. Reports indicate a high proportion of patients with feeding difficulties who have undergone esophagogastroduodenoscopy (EGD), demonstrate some degree of inflammation on biopsies [4,13], with a subset including those with eosinophilia [14].…”
Section: Introductionmentioning
confidence: 99%
“…We calculated pooled mean difference (MD) and 95% confidence intervals (CI) for the cell counts in those with rumination syndrome and the control group using a random-effects model. 3 We identified 1003 studies; after the removal of studies that did not meet the inclusion criteria, two studies (50 cases, 20 controls) were analysed 4,5 ; results are in Table 1. On pooled analysis, those with rumination syndrome had on average more eosinophils per five highpower fields than controls.…”
mentioning
confidence: 99%